Peran Kepemimpinan Pendidikan untuk Mewujudkan Tujuan Pendidikan - Paulinus Kanisius Ndoa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2025)
Leaders at any level and in any organization are needed to organize and mobilize various resources in the organization in order to achieve the goals of the organization. Likewise in the context of educational organizations. The leaders of universities and school principals play a very important role in leading, organizing, mobilizing and managing the educational institutions they lead in order to create quality education. This research was conducted with a literature approach, where researchers examined various theoretical studies from experts on leadership in general, educational leadership and the findings of previous researchers related to the role and influence of educational leadership on achieving the goals of educational organizations. From various literatures, it can be concluded that the quality of leadership possessed by an educational leader substantially influences the success of an educational institution. The type and style of leadership they have and apply also determine the effectiveness and speed of an educational institution in achieving the vision and mission as outlined by the educational institution.